Efektivitas dan Efisiensi Penerapan Rekayasa Sistem Pengelolaan Reservasi Gedung Aula Berbasis Kepuasan Pengguna Sistem - Prayitno, Seno Wiji; Darsanto; Margana, Ferry Kurniawan (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2025)
The hall is a place used to hold events with a large space. Hall reservations are made by contacting the manager directly or coming directly to the hall building. This research aims to build a hall reservation management system and make it easier for tenants to make reservations online. The research was conducted using descriptive statistical methods with the Rational Unified Process (RUP) as a system development framework. White box and black box testing are alpha system testing. ISO 9241-11 standard and heuristic evaluation as system beta testing. White box testing begins with creating a flow graph, calculating cyclomatic complexity, and determining independent paths. While the black box starts by determining the test case and expected results, the actual results will be obtained. The results of measuring the usability level with ISO 9241-11 obtained an effectiveness level value of 100%, an efficiency level value of 100% with a total time of about 594 seconds, and a user satisfaction level value of 73 with a good category, grade B scale, acceptable description and passive NPS. The results of the heuristic evaluation obtained that there are still problems with the system, and each problem has a different problem severity rating.